The Design, Implementation, and Acceptability of a Telehealth Comprehensive Recovery Service for People With Complex Psychosis Living in NYC During the COVID-19 Crisis - Lynch, David A.; Medalia, Alice; Saperstein, Alice (Frontiers in Psychiatry, 2020)
Introduction: The COVID-19 crisis and subsequent stay-at-home orders have produced unprecedented challenges to the dissemination of recovery oriented behavioral health services (RS) that support the treatment of those with complex psychosis (CP).This population has typically been managed with in-person pharmacotherapy and/or RS, with the goals of symptom relief, improved life satisfaction and increased community engagement. COVID-19 related social distancing measures have required rapid shifts in care management, while easing of telehealth regulations has allowed for flexibility to approach RS differently. It is essential to learn from the RS telemedicine implementation experience, so that RSs can maintain care for this vulnerable and needy population. Method: This paper describes the successful telehealth conversion of a NYC-based, university affiliated RS that serves adults with severe mental illnesses (SMI; n = 64). Results focus on the telehealth acceptance rates of the subset of participants with CP (n = 23). Results: The RS continued providing services including intake, care coordination, group psychotherapies, skills training groups, individual skills coaching, and vocational/educational supports. The telehealth conversion rates of the CP subsample indicated that 90% CP patients accepted telehealth sessions and maintained their specific treatment plans in the virtual format. Mean comparisons between session attendance and cancellations/no-shows during the six-week period before and after telehealth conversion showed no significant differences in service utilization. Discussion: RSs play an essential role in the treatment of CP and telehealth may prove to be a viable format of care delivery even after the COVID crisis subsides. The multiple factors in the inner and outer treatment setting that contributed to successful conversion to telehealth will be considered along with the challenges that clinicians and patients encountered.